2015
DOI: 10.3109/13880209.2015.1085580
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective activity of chloroform extract ofMuntingia calaburaandMelastoma malabathricumleaves

Abstract: CEMC and CEMM exert gastroprotective effects in animals with ethanol-induced gastric ulcers via antioxidant and anti-secretory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…One of the plants in Malaysia that has been used traditionally by the Malay to treat gastric ulcer is M. malabathricum and studies have demonstrated the gastroprotective potential of the aqueous [ 21 ], chloroform [ 22 ], and methanol [ 7 , 16 ] extracts of its leaves. The methanolic extract showed the ability to attenuate ethanol- and indomethacin-induced gastric ulcer in rats [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the plants in Malaysia that has been used traditionally by the Malay to treat gastric ulcer is M. malabathricum and studies have demonstrated the gastroprotective potential of the aqueous [ 21 ], chloroform [ 22 ], and methanol [ 7 , 16 ] extracts of its leaves. The methanolic extract showed the ability to attenuate ethanol- and indomethacin-induced gastric ulcer in rats [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric ulcer is one of the most prevalent chronic diseases of the gastrointestinal tract [1, 2]. The main causes of gastric mucosal damage are infection by Helicobacter pylori , the administration of steroidal and nonsteroidal anti-inflammatory drugs (NSAIDs), stress, smoking, alcohol consumption, and nutritional deficiencies [3]. Many people are exposed to these risks, so they are vulnerable toward acquiring associated diseases, such as gastritis, that may develop into gastric ulcers [4].…”
Section: Introductionmentioning
confidence: 99%
“…Typical treatments for gastric ulcers are acid suppressant drugs, such as type-2 histamine receptor antagonists and proton pump inhibitors [2], but they have some adverse effects. Long-term use of acid suppressants can lead to gynecomastia, impotence, osteoporotic bone fracture, and deficiencies of iron and magnesium, as well as vitamin B 12 hypergastrinemia after discontinuation [3, 8, 9]. Gastric ulcers frequently recur and the symptoms last for a long time [5]; therefore, there is a need for drugs that can be taken long-term with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Another attempt in the same year, made by Aligita ) scavenging assay, oxygen radical absorbance capacity (ORAC) assay, total phenolic content to determine the antioxidant potential of leaves and reported that the chloroform extract of leaves contains strong antioxidant activity. To determine the gastroprotective activity of this extract, they employed ethanol-induced and pylorus ligation induced ulcer models and reported a dosedependent gastroprotection 13 . In the same year, Zakaria et al (2016) conducted another research to determine the gastroprotective mechanism of ethyl acetate fraction from the methanolic extract of Muntingia calabura leaves on experimental male Sprague Dawley rats.…”
Section: Fig 2: Uses Of Muntingia Calabura Worldwidementioning
confidence: 99%